A Sociocultural Exploration of Shame and Trauma Among Refugee Victims of Torture - Womersley, Gail (Cham: Springer, 2019)
Shame profoundly colours the experiences of the thousands of refugees entering Europe. Not only does the literature attest to the high levels of trauma among this population, research in the past decade has increasingly revealed the hidden yet pervasive role that shame may play in posttraumatic symptomatology. Shame may emerge as a result of the many forms of torture, sexual violence and other atrocities experienced in the country of origin, yet is equally exacerbated by degrading and humiliating asylum procedures, having to accept a new and often devalued social identity of being an asylum seeker, and the embarrassment of not meeting culturally-informed expectations to financially support the family back home. Shame is a complex process affecting core dimensions of the self, identity, ego processes, and personality—and is thus inextricably shaped by culture. It has a detrimental impact on health-seeking behaviour, yet its masked manifestations remain often unnoticed by practitioners. This is a critical consideration for clinicians and researchers working with refugee populations, where the relation is typically marked by power differentials across a matrix of identities informing not only the shame of the refugee but of the clinicians or researchers themselves. As both a researcher and clinical psychologist working with refugee populations, I explore the myriad dimensions of shame within this context based on personal reflections of my time “in the field” as well as the burgeoning literature on this topic. Key implications for techniques and methods which may be drawn upon by both researchers and clinicians are discussed.
Keywords: Refugees Trauma Culture Migration Asylum Shame